1978
DOI: 10.1111/j.1365-2621.1978.tb02292.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Mechanically Deboned Beef in Cooked Salami

Abstract: Cooked salami possessing 0, 10, 20 and 30% levels of mechanically deboned beef (MDB) was evaluated at 0, 14, 28, 42 and 56 days of salami storage at 6°C. A consumer panel, a descriptive attribute panel and a flavor profile panel found less desirable flavor, juiciness, tenderness and texture scores in salami containing 20 and 30% levels of MDB. Flavor profile panel results indicated higher aroma and flavor intensities and more rancid flavors, with increased level of MDB and length of storage time. Microbial cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Field et al (1974a) indicated that panels prefer bologna made from hand deboned meat in the area of tenderness. Joseph et al (1977) found consumers prefer the tenderness and texture of hand deboned meat used to make cooked salami. Marshall et al (1977) also found that frankfurters containing 20-40s mechanically deboned pork were very mushy.…”
Section: Methods Of Boningmentioning
confidence: 99%
See 1 more Smart Citation
“…Field et al (1974a) indicated that panels prefer bologna made from hand deboned meat in the area of tenderness. Joseph et al (1977) found consumers prefer the tenderness and texture of hand deboned meat used to make cooked salami. Marshall et al (1977) also found that frankfurters containing 20-40s mechanically deboned pork were very mushy.…”
Section: Methods Of Boningmentioning
confidence: 99%
“…In other work, a triangle test indicated no significant flavor difference (P>O.O5) existed in bologna containing 10% machine deboned versus 10% hand deboned meat (Field and Riley, 1972). When using mechanically deboned beef in a cooked salami product, flavor profile and panel results indicated higher aroma and flavor intensities and more rancid flavor with increased levels of mechanically deboned meat and with increased lengths of storage (Joseph et al, 1977(Joseph et al, , 1978. Field et al (1974a) and Anderson and Gillett (1974) found that there was no significant difference in emulsifying capacity or emulsifying stability between hand deboned meat and mechanically deboned meat from the whole carcass.…”
Section: -Journalmentioning
confidence: 99%
“…The possible use of mechanically processed (red meat species) product has been reported in cooked salami (Joseph ^ al., 1978), dry fer mented salami (Berry ^ al., 1979), ground beef (Cross et £l., 1977;Seideman et al, 1977;Emswiler, et al, 1978;and Cross ^ al. , 1978a), and bologna (Field et £l., 1974a;Chant ^al., 1977;and Misock ^ al., 1979).…”
Section: Chemical and Physical Characteristics Of Frankfurters Preparmentioning
confidence: 99%
“…The use of mechanically deboned red meat has been studied in cooked salami (Joseph et al, 1978), dry fermented salami (Berry et al, 1979), groimd beef (Cross et al, 1977Seideman et al, 1977), bologna (Field et al, 1975;Chant et al, 1977;Misock et al, 1979) and frankfurters (Bushway et al, 1982;McMillin et al, 1980;Meiburg et al, 1976;Marshall et al, 1977). McMillin et al (1980) reported that frankfurters containing 30% or less mechanically separated pork (MSP) were similar in smoke house jdelds and percentage of water and fat lost during processing compared to frankfurters containing 40% or 50% MSP.…”
Section: Introductionmentioning
confidence: 99%
“…Formulation (level of MDB) and storage time had no significant effect on any of the palatability traits evaluated. Joseph et al (1978) A study by Cross et al (1977) on the palatability of groimd beef patties containing different levels of MDB indicated that patties containing 5, 10, 15 and 20% MDB were considered more acceptable than the control. As the percentage of added MDB increased, panel ratings for tenderness and juiciness increased.…”
Section: Introductionmentioning
confidence: 99%